Perception of community residents on supporting urban agriculture in Malaysian city : case study at Bukit Mertajam - Pushpawani Ramaloo; Liong, Choong-Yeun; Chamhuri Siwar; Anizan Isahak (Penerbit Universiti Kebangsaan Malaysia, 2018)
The purpose of this study is to identify the concept of urban agriculture in the residential environment of a community by taking the Taman Desa Damai community of Bukit Mertajam City, Penang State, Malaysia as the sample. This study conducted in-depth interviews and observations with 15 community residents to explore the influences of setting up urban agriculture with respect to three aspects of community residents benefits at the social, economics and environmental levels, and followed by about future farm environmental effect, key stakeholders and the challenges. The results indicate that community farming has become significant in realizing the full potential of the residential community and facing obstacles to be sustained in the long term. We recommend stakeholders to support in terms of finance so that community farming has more access to technical facilities and achieve household food self-sufficiency, food availability and food security, diversity of diet and contribute immensely to urban household’s livelihoods. It is hoped that this work will be a useful reference in promoting more urban community participation in community urban agriculture in order to achieve sustainable urban environment.